THE VIOLATION OF MAXIM RULES IN KETOPRAK HUMOR - Muh Imam Shofwan (Universitas Muria Kudus, 2018)
The investigation in fact aimed mainly to analyze the theory of conversational implicature proposed by austin and later on extended by grice’s principle maxim which can be universal and applied to all languages of the world, including java language art show of ketoprak entitled “joko kendil”. The study is expected to be beneficial to the world of literature. In addition, the writer hopes that the result of the study will also give additional information to the reader and contribute to the development of literary study particularly among students who are interested in the literary study. Twenty-three minutes recorded video conversation of all participants of the show data were transcribed into written form and translated into english. Needless to say, the analysis of the data has been based on both austin’s and grice’s principles of pragmatics, conversational implicature theory. Illustrative examples for flouting the four maxims of speech were introduced and analyzed pragmatically. Particularly the research was objected to find out the violation of maxims of quantity, quality, manner and relation flouted and an implicature from each generated. From the analysis, it was found that the claim of “ketoprak” speech can be systematized and it has implicatures in one way but not in another is to some extent true. Thus, this theory can be applied to other java language idiolects.